Electrochemistry of Dinuclear Organometallic [5]Trovacenyl Derivatives Bridged by Group 14 Elements (Si, Ge, Sn, Pb)1. Issue 1 (30th November 2016) - Lu, Feng; Harms, Klaus
Abstract : Group 14 elements (Si, Ge, Sn, and Pb) were applied as spacers to construct new dinuclear organometallic [5]trovacenyl derivatives [(η 7 ‐C7 H7 )V(η 5 ‐C5 H4 )]2 MR2 (2 ··, 3 ··, 4 ··, and5 ·· ; M = Si, Ge, Sn, Pb; R = Me or Ph), which have been characterized by mass spectrometry, elemental analysis, and/or X‐ray diffraction analysis. A systematic electrochemical study by cyclic voltammetry indicates weak intramolecular electronic communication between two vanadium centers in the order of Si (2 ·· ) < Ge (3 ·· ) < Sn (4 ·· ) < Pb (5 ·· ). The impact of the substituents and the solvents on the electrochemical behavior of [(η 7 ‐C7 H7 )V(η 5 ‐C5 H4 )]2 SnMe2 (5 ·· ) and [(η 7 ‐C7 H7 )V(η 5 ‐C5 H4 )]2 SnPh2 (9 ·· ) was evaluated. Abstract : The electrochemistry of dinuclear [5]trovacenyl derivatives [(η 7 ‐C7 H7 )V(η 5 ‐C5 H4 )]2 MR2 (2 ··, 3 ··, 4 ··, and5 ··, M = Si, Ge, Sn, Pb; R = Me or Ph) bridged by group 14 elements (Si, Ge, Sn, and Pb) was investigated systematically by cyclic voltammetry. The results indicate that the strength of the weak intramolecular electronic communication between the two V centers is in the order of Si (2 ·· ) < Ge (3 ·· ) < Sn (4 ·· ) < Pb (5 ·· ).